PATHOPHYSIOLOGICAL ASPECTS OF GOAT FALSE PREGNANCY (HYDROMETRA) AND MODERN METHODS OF ITS DIAGNOSIS AND THERAPY - Dyulger G.P.; Stekolnikov A.A.; Shatsky K.O.; Leontеv L.B.; Dyulger P.G.; Sedletskaya E.S.; Latynina E.S.; Akchurina I.V (Scientific Journal of Pedagogy and Economics, 2020)
The article considers the unique, not described in the domestic scientific and educational literature, the dishormonal pathology of the reproductive sphere of goats. The disease is characterized by prolonged anaphrodisia, the persistence of one or more functionally active corpus luteum in the ovaries and hydrometra - volumetric increase in the size of the uterus due to effusion of sterile serous fluid into its cavity. Hydrometra is a leading diagnostic sign of the disease. The research aimed to analyze the data of foreign literature on epidemiology, pathophysiology, diagnostics, and therapy of false pregnancy (hydrometra) in goats. Based on the analysis of foreign literature data, the epidemiological characteristics of the disease were determined. It was found that the hydrometra is a fairly common pathology and is recorded on average in 4.2% of goats. The risk group includes goats aged 6...8 years and older. A hereditary (familial) predisposition of milk goats to the development of hydrometra was revealed. Iatrogenic factors also have a significant effect on the frequency of incidence: hormonal treatment of goats during and/or out the estrous season with progestins alone or in combination with gonadotropin in the serum of mares. The etiology of pseudopregnancy, as well as the cause-effect relationship between the persistence of the corpus luteum and the development of hydrometra have not been fully established. Retention of the corpus luteum always precedes and accompanies the development of hydrometra. Spontaneous regression of the persistent corpus luteum leads to interruption of pseudopregnancy and emptying of hydrometra. Violation of the external regulation with prostaglandin of the functional activity of the corpus luteum, apparently, plays a pivotal role in the pathogenesis of the disease. According to the profile of progesterone in the blood, it was found that the duration of false pregnancy is an average of 150.3±23.5 days. Visual echography is the main diagnostic method of false pregnancy. The diagnosis of the disease is based on the detection of hypoechoic fluid in the uterine cavity in the absence of placentas and fetuses in the uterus. Prostaglandin therapy is a pathogenetically substantiated and quite effective method of treating hydrometra.